Post-traumatic stress disorder symptoms and underaged refugees and the role of ICTs. - Stathopoulou, Agathi; Pantiri, Kristalia Marina; Salapata, Giolanta (Eximia, 2022)
War and political conflicts are forcing a significant portion of the world's population to leave their homeland and move to another state. Among these individuals are underage refugee asylum seekers. Minor refugees are a social group facing psychosocial difficulties. The development of different forms of psychopathology is observed in the population of refugee children and adolescents. Among the mental disorders that occur in minors is Post-Traumatic Stress Disorder (PTSD). The disorder causes disfunction on the daily functioning of individuals and obstacles to their normal psychosocial development. The purpose of this study is to highlight and understand the clinical entity of PTSD that appears in this minority group. The methodology on which the work was based is the systematic literature review. The conclusion that emerges concerns the effects of the war on the development of PTSD symptoms in refugee children and adolescents. Finally, the conclusions of the review emphasize the important role that mental resilience plays in the effective treatment of trauma.